"Forebodings about fascism": Marion Milner and Virginia Woolf. Issue 1 (2nd January 2021) - Tyson, Helen
ABSTRACT: In A Life of One's Own (1934) Marion Milner asked the apparently simple question: "What do I like?" By 1937, however, when Milner published An Experiment in Leisure, the question "What do I like?", and the urgency of answering it, had shifted. Writing against the backdrop of a rising current of fascism across Europe, there was a new urgency for Milner, in 1937, in understanding the apparent ease with which, not only Hollywood movie-makers, but now also European dictators might manipulate individual desires. Focusing on portraits of reading from Virginia Woolf's 1937 novel, The Years, alongside Milner's 1937 An Experiment in Leisure, this article explores Woolf's and Milner's shared—and deeply anxious—fascination with what Milner described, in her 1950 book On Not Being Able to Paint, as the "Monsters within and without." This article tracks Woolf's and Milner's encounters with the internal and external "monsters" haunting 1930s Europe, showing how, for both writers, the historical vicissitudes of fascism traversed the terrains of psychic, cultural, and political life. Both Woolf and Milner, I argue, were engaged in an endeavor to understand the entanglement of the psychic, social and political forces at work in our everyday acts of leisure and reading.